Quantitative clinical characteristics of 53 patients with MPS VII: a cross-sectional analysis - Zielonka, Matthias; Garbade, Sven; Kölker, Stefan; Hoffmann, Georg F.; Ries, Markus (Genetics in medicine, 2017)
Purpose:The main purpose of the study was to provide quantitative data regarding survival and diagnostic delay. Mucopolysaccharidosis (MPS) type VII (OMIM 253220) is a progressive neurometabolic disorder caused by deficiency of the lysosomal enzyme β-glucuronidase (GUS). Hard clinical end points have not been quantitatedMethods:We quantitatively analyzed published cases with MPS VII (N = 53/88 with sufficient data). Main outcome measures were onset of disease and survival. The role of biomarkers such as GUS residual enzyme activity and levels of storage material assessed as urinary excretion of glucosaminoglycans (GAG) as potential predictors of clinical outcomes were investigated. The analysis was conducted according to STROBE criteria.Results:Median survival of the postnatally diagnosed population was 42 months. Median age of disease onset was the first day of life; median age at diagnosis was 11 months. Hydrops fetalis was frequent. Patients with residual GUS activity in fibroblasts more than 1.4% or urinary GAG excretion less than 602% of normal survived longer than patients with GUS enzyme activity below or GAG excretion above these thresholds.Conclusion:MPS VII has its disease onset prenatally. In the absence of a prenatal diagnosis, most cases are clinically apparent at birth. Our data corroborate a phenotype-biomarker association in MPS VII. The survival data characterize the natural history with important implications for therapeutic studies.Genet Med advance online publication 06 April 2017